Methodological substantiation of the penalty for the damage to the resort recreational potential - Marina V. Anashkina, Kostyantyn A. Malyshenko, Vadim A. Malyshenko, (Opción, 2020)
The purpose of the study is to develop a methodological substantiation of the penalty for the damage to resort recreational potential. The study revealed the lack of a single system for solving the problem of preserving and developing the recreational potential of the territories. According to the results, a penalty calculation methodology was developed. The application of the methodology will solve the inconsistency between the administrative liability and the damage to the recreational potential of the territory and act as a preventive measure, which will make it possible to compensate for the losses of the resort and exercise effective control over its safety and development.